2005
DOI: 10.1109/tsp.2005.849154
|View full text |Cite
|
Sign up to set email alerts
|

Linear prediction approach for efficient frequency estimation of multiple real sinusoids: algorithms and analyses

Abstract: Abstract-Based on the linear prediction property of sinusoidal signals, two constrained weighted least squares frequency estimators for multiple real sinusoids embedded in white noise are proposed. In order to achieve accurate frequency estimation, the first algorithm uses a generalized unit-norm constraint, while the second method employs a monic constraint. The weighting matrices in both methods are a function of the frequency parameters and are obtained in an iterative manner. For the case of a single real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 22 publications
1
85
0
1
Order By: Relevance
“…Both the STLS2 and proposed algorithms terminate when the difference of norm of successiveâ is less than 10 −6 or the number of iterations has reached the maximum allowable value, which is set to 10. The initial value ofx is obtained by a simple consistent method [22] and that of Δx is set to 0 ×1 for both algorithms.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Both the STLS2 and proposed algorithms terminate when the difference of norm of successiveâ is less than 10 −6 or the number of iterations has reached the maximum allowable value, which is set to 10. The initial value ofx is obtained by a simple consistent method [22] and that of Δx is set to 0 ×1 for both algorithms.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…So and Chan [4] have shown that the PHD estimation performance can be improved if the data matrix is employed instead of the covariance matrix. By incorporating the technique of weighted least squares (WLS) into [4], the resultant algorithm [5] can provide optimum accuracy. Recently, Elasmi-Ksibi et al [6] have also extended [3] with the use of a normalized second-order infinite impulse response notch filter, whose frequency variance can attain Cramér-Rao lower bound (CRLB) [1] when ω is close to 0.5π.…”
Section: Introductionmentioning
confidence: 99%
“…Although single-tone frequency estimation has been well studied, efforts have continually been made to devise fast and accurate estimators with small threshold signal-to-noise ratio (SNR) and uniform estimation performance across the admissible frequency range. In this work, we propose to exploit the principal-singular-vector utilization for modal analysis (PUMA) [14] which is originally derived for two-dimensional sinusoidal parameter estimation, and WLS [5], in the frequency estimator development, in order to fulfil the above-mentioned challenges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations